Economic comparison of growing different willow cultivars. (October 2015) - Stolarski, Mariusz J.; Rosenqvist, Håkan; Krzyżaniak, Michał; Szczukowski, Stefan; Tworkowski, Józef; Gołaszewski, Janusz; Olba-Zięty, Ewelina
Abstract: The aim of this study was to assess the cost, income and revenue of chips produced from seven new willow cultivars harvested in three-year harvest rotations. In the base scenario, the willow biomass yield varied greatly from one cultivar to another and the cost of producing chips ranged from 89.1 € Mg −1  d.m. to 57.1 € Mg −1  d.m. for UWM 155 and UWM 006, respectively. The highest revenue in the base scenario (537 € ha −1  year −1 ) was achieved in the plantation with the highest-yielding cultivar UWM 006. A sensitivity analysis showed that the change in the biomass price and change in energy content of willow biomass had a much greater effect on the final revenue than a change in the yield level. When the price increased by 10%, the revenue from growing different cultivars increased by 33–92%, whereas when the yield increased by 10%, the revenue from growing different cultivars increased by 13–20%. Shortening the transport distance from 50 to 25 km increased the final revenue by 14–36%. An increase in the transport distance to 100 km decreased the final revenue by 28–73%, and when the transport distance increased to 200 km, only the production of UWM 006 and UWM 043 cultivars brought any positive revenue. It is important to find willow varieties with a high energy content because a higher yield of Mg d.m. per hectare will cause the costs per hectare increase but the costs per Mg d.m. and GJ will decrease. Highlights: This study presents the production cost effectiveness of 7 new willow cultivars. The highest revenue from the studied cultivar was achieved for the UWM 006 cultivar. Production cost of chips varied for the base case from 89.1 to 57.1 € Mg −1  d.m. The cost of generating 1 GJ ranged from 3.4 to 5.7 € GJ −1 . When the price of chips increased by 10%, the revenue increased by 33–92%.